Some Junctures in the Evolution of the Process of Establishing Accounting Principles in the U.S.A. : 1917-1972. - Zeff, Stephen A. (The Accounting Review, 1984)
ABSTRACT: This paper reviews the circumstances attending five major turning points in the process by which accounting principles have been established in the United States. Particular attention is directed to the apparent reasons why the new approaches or reforms were undertaken. The review, which covers a 56-year period, concludes that generalizations about the factors that were influential in the shaping of the decision-making process, especially over so long a period, are difficult to make. Nonetheless, a motivating force seems to have been the accounting profession's fear of government involvement. The American Accounting Association is seen to have played a role at several of the junctures.